2000
DOI: 10.1200/jco.2000.18.3.584
|View full text |Cite
|
Sign up to set email alerts
|

Early Start of Adjuvant Chemotherapy May Improve Treatment Outcome for Premenopausal Breast Cancer Patients With Tumors not Expressing Estrogen Receptors

Abstract: In premenopausal patients with ER-absent tumors, early initiation of systemic chemotherapy after primary surgery might improve outcome. Further confirmatory studies are required before any widespread modification of current clinical practice. In premenopausal patients with tumors expressing some ER, gains from early initiation are unlikely to be clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(106 citation statements)
references
References 31 publications
5
101
0
Order By: Relevance
“…However, the study published by Colleoni et al (2000b) defined an ER-absent group as one with 0% cells positive and ER positive when X1% of cells stained positive. Similarly, the IBCSG has previously defined three groups on the basis of ER content: ER absent, ER low (1 -9 fmol mg À1 cytosol protein) and ER positive (X10 fmol mg À1 cytosol) (Colleoni et al, 2000a). This was based on data showing a better prognosis for tumours with as few as 1% of cells staining positive when treated with tamoxifen (Harvey et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study published by Colleoni et al (2000b) defined an ER-absent group as one with 0% cells positive and ER positive when X1% of cells stained positive. Similarly, the IBCSG has previously defined three groups on the basis of ER content: ER absent, ER low (1 -9 fmol mg À1 cytosol protein) and ER positive (X10 fmol mg À1 cytosol) (Colleoni et al, 2000a). This was based on data showing a better prognosis for tumours with as few as 1% of cells staining positive when treated with tamoxifen (Harvey et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…According to steroid hormone receptor status tumors were classified as highly endocrine responsive (ER and PgR C50% of the cells positive), incompletely endocrine responsive (ER or PgR 0-49% of the cells positive) and endocrine non responsive (ER and PgR 0% of the cells positive). The cut off used for the selection of endocrine non responsive patients (0% of the cells) was based on previous studies indicating a different response and outcome after PCT and adjuvant therapy for this patient population if compared with those patients whose tumors had some expression of steroid hormone receptors [7,13]. The cutoff of 50% of positive cells for ER and PgR used for defining highly endocrine responsiveness was arbitrarily selected according to the results of retrospective analysis of several trials (SWOG Intergroup 0100, IBCSG trials VIII and IX) asking the question of the addition of adjuvant chemotherapy to endocrine therapy.…”
Section: Pathology and Immunohistochemistrymentioning
confidence: 99%
“…9, 10 More recently, a larger study analyzed the effect of timing of cyclophosphamide, methotrexate, and fluorouracil (CMF) chemotherapy on survival in premenopausal patients participating in the International Breast Cancer Study Group (IBCSG) trials I, II, and VI. 11 This study found a significant and clinically striking improvement in 10-year DFS in a small subset of premenopausal patients with estrogen receptor (ER)-absent tumors who started chemotherapy within 21 days of surgery compared with those commencing chemotherapy 21 days or more following surgery (60% v 34%; P ϭ .0003). No similar benefit was seen for other patients (the majority).…”
mentioning
confidence: 76%
“…11 In this analysis, there was heterogeneity in the duration and total dose of chemotherapy received. A remarkable improvement in 10-year DFS (60% v 34%) was found for a small subgroup of premenopausal patients with node-positive, ER-absent tumors receiving CMF chemotherapy (226 of It should be noted that patients who had received adjuvant oophorectomy or other endocrine therapy were excluded from the IBCSG study, whereas 84% of our patients also received endocrine therapy (nearly always tamoxifen) given concurrently with chemotherapy.…”
Section: Discussionmentioning
confidence: 98%